Evaluation of a combined cooling, heating, and power system based on biomass gasification in different climate zones in the U.S. (1st February 2018) - Li, C.Y.; Wu, J.Y.; Shen, Y.; Kan, X.; Dai, Y.J.; Wang, C.-H.
Abstract: A combined cooling, heating, and power system based on biomass gasification is modeled via experiment and its performance is evaluated. The system operation is simulated using load data of small offices located in different climate zones in the U.S. The operation strategy comprises following the electric load (FEL) and following the thermal load (FTL). Based on the operation data, energetic, economic, environmental, and overall performances of the system are evaluated. Results show that the annual integrated performance ( S whole ) of the system ranges from 0.229 to 0.473 in FEL mode and from 0.067 to 0.457 in FTL mode, in different regions. The system has a better performance in FEL mode, and is more attractive to install in the regions with more thermal load. Furthermore, the match degree of heat to power ratio between load and output also has an effect on the system performance. Sensitivity analysis shows that the system performance is more sensitive to the cost of biomass, cost of grid electricity and CO2 emission rate of the grid in both modes, and COP of thermally activated chiller in FTL mode. By changing the above-mentioned parameters, S whole can be improved by up to 13.7%, 8.2%, 11.0%, and 19.7% respectively. Highlights: A CCHP system based on biomass gasification was evaluated. The performance of the system in different climate zones was compared. Evaluation comprised energy, economic and environmental aspects. The system has better performance when there is much thermal load.